(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, theoretical and experimental methods have been developed for obtaining and studying effective thermomechanical characteristics - residual stresses and deformations in panels made of nanomodified materials with an asymmetric reinforcement scheme. The study of the residual stress-strain state of structural elements made of carbon fiber reinforced plastic using the values ​​of thermoelastic characteristics of composite monolayers identified on the basis of the developed methods made it possible to reveal the possibility of reducing the residual stress-strain state in structures with asymmetric reinforcement schemes.